1987
DOI: 10.1128/iai.55.8.1743-1750.1987
|View full text |Cite|
|
Sign up to set email alerts
|

Mechanisms of platelet aggregation by viridans group streptococci

Abstract: The direct aggregation of platelets is thought to be an important event in the pathogenesis of viridans streptococcal endocarditis, but the mechanisms for platelet activation are unknown. We evaluated the processes by which two endocarditis-producing strains of viridans group streptococci activated human platelets in vitro, as measured by platelet cyclooxygenase activity, secretion, and aggregation. Addition of either streptococcal strain to platelets suspended in whole plasma resulted in a mean lag phase of 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
48
0
1

Year Published

1991
1991
2017
2017

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 95 publications
(51 citation statements)
references
References 45 publications
2
48
0
1
Order By: Relevance
“…Furthermore, a 150 kD protein, which possesses a 'collagen-like' domain, has been isolated from a strain of S. sanguis Erickson et al, 1992), and appears to interact with a 175 kD protein, possibly complexed with the main collagen receptor on the platelet membrane, glycoprotein Ia (GPIa) (Gong et al, 1995). As well as this, we have previously shown the involvement of at least two other membrane receptors, GPIb and GPIIb/IIIa (the integrin platelets to bacteria (Ford et al, 1993;Herzberg et al, 1983a;Sullam et al, 1987). Washed platelets are not aggregated by S. sanguis (Ford et al, 1993).…”
mentioning
confidence: 71%
See 1 more Smart Citation
“…Furthermore, a 150 kD protein, which possesses a 'collagen-like' domain, has been isolated from a strain of S. sanguis Erickson et al, 1992), and appears to interact with a 175 kD protein, possibly complexed with the main collagen receptor on the platelet membrane, glycoprotein Ia (GPIa) (Gong et al, 1995). As well as this, we have previously shown the involvement of at least two other membrane receptors, GPIb and GPIIb/IIIa (the integrin platelets to bacteria (Ford et al, 1993;Herzberg et al, 1983a;Sullam et al, 1987). Washed platelets are not aggregated by S. sanguis (Ford et al, 1993).…”
mentioning
confidence: 71%
“…Oral streptococci are the most common causative agents of IE and among these Streptococcus sanguis and S. oralis are the most frequent . There have been several reports that S. sanguis can directly aggregate platelets in vitro (Douglas et al, 1990;Herzberg et al, 1983a;Manning et al, 1994;Sullam et al, 1987) but the mechanisms by which this occurs are not entirely clear. Previous work has shown that (i) there is a lag between the addition of bacteria and the onset of aggregation, the period of which varies between subjects (Ford et al, 1993;Herzberg et al, 1990), (ii) platelets must be functional (Ford et al, 1993;Herzberg et al, 1983a), and (iii) that bacterial interaction with platelets results in true aggregation accompanied by secretion of granule contents (Ford et al, 1993;Herzberg et al, 1983a).…”
mentioning
confidence: 99%
“…Of course commensals may take advantage of such mucin binding to remain within their preferred ecological niche (797)(798)(799)(800) and to favor dental biofilm development (801). But on the rare occasions when such bacteria accidentally find their way into the bloodstream, these same commensalism-favoring adhesins become virulence factors, mediating interactions with platelets, which act as carriers of the organisms to eventual infection of damaged heart valves (798,(802)(803)(804)(805)(806)(807). This is a recurring theme at sites of interspecies interactions, wherein factors favoring routine commensalism turn into potent "virulence factors", on the occasions when physical barriers are breached and/or host immunity is compromised.…”
Section: Host Decoysmentioning
confidence: 99%
“…Among microorganisms possessing the ability to induce platelet aggregation in PRP, Gram-positive cocci, S. aureus, S. sanguis, and group A streptococci have been studied in detail (8,18,24,28,35,36,39,43). Concerning the interaction between enterococci and platelets, more detailed investigations have been needed for comparison with other bacteria-platelets interaction, although Clawson et al (8) reported some properties of the platelet aggregation.…”
Section: Discussionmentioning
confidence: 99%
“…The mechanisms of platelet aggregation by these stimuli have been studied in detail (16). In contrast to these effects favorable for hemostasis, platelets also possess a pathogenic significance in disseminated intravascular coagulation (DI C) during sepsis or infective endocarditis (3,7,22,30) and observations have been made concerning the relationship between the platelet and several species of microorganisms, Staphylococcus aureus (8,18,28,40), coagulasenegative staphylococci (CNS) (41), streptococci (24,35,36,39,43), Listeria monocytogenes (9), Fusobacterium necrophorum (15), Aspergillus fumigatus (31), Candida albicans (33), Histoplasma capsulatum (10).…”
mentioning
confidence: 99%